(3JSgjd GdefGaY aj GdWH hGdMceI GdeTJed Ydi TaGA GdCLSGe hcJGH GdQMeIs - (3GdGRQbj , EHQGgje Hf YHO GdQMef Hf CHj HcQ GdGRQbj Gdjefj,J (B815 (3g` s ((3CMeO Hf Ydi Hf eMeO GdLdGd s)
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi Yf GdCfOGO CeG HYO aEf GdWH Yde YXje faYg adeG QCjJ GdeYJfi Hg bdjdkG afTWfi Pdc Edi LeY TF ef gPG Gdaf s
(3BNQgG (B:s
(3gPG GdZdGe hgPg GdCeI hgPg GdOGHI CVjb ef LdO Led , hGddg CYde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B172 - (3U(B309s
(3GdeMJhi Ydi TaGA GdGLSGe hcJGH GdMQeIs
(3YdjgG JbjjOGJ cKjQIhQbI GdNWHI eYGOI dEVWQGHgG hENJdGWgG HhQbI ef GdcJGHs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdWHs